Unleashing giant Förster resonance energy transfer by bound state in the continuum - Yuan, Zhiyi (2025)
Förster resonance energy transfer (FRET), driven by dipole-dipole interactions (DDIs), is widely utilized in chemistry, biology, and nanophotonics. However, conventional FRET is ineffective at donor-acceptor distances exceeding 10 nm and measurements suffer from low signal-to-noise ratios. In this study, we demonstrate significant FRET enhancement and extended interaction distances under ambient conditions by utilizing a bound state in the continuum (BIC) mode within a dielectric metasurface cavity. This enhancement is achieved by leveraging the ultrahigh quality factors, minimal material absorption, and nonlocal effects associated with the BIC mode. Spectrally and angularly resolved photoluminescence (PL) lifetime measurements reveal that the BIC mode significantly increases the FRET rate and interaction distance. The FRET rate is enhanced by up to 70-fold, and the interaction distance is significantly boosted by over an order of magnitude, reaching ∼100 nm. These findings offer valuable insights for achieving long-range, high-efficiency FRET and collective DDIs using loss-less dielectric metasurfaces.